2012
DOI: 10.3389/fpls.2012.00169
|View full text |Cite
|
Sign up to set email alerts
|

MAP Kinase Cascades in Arabidopsis Innate Immunity

Abstract: Plant mitogen-activated protein kinase (MAPK) cascades generally transduce extracellular stimuli into cellular responses. These stimuli include the perception of pathogen-associated molecular patterns (PAMPs) by host transmembrane pattern recognition receptors which trigger MAPK-dependent innate immune responses. In the model Arabidopsis, molecular genetic evidence implicates a number of MAPK cascade components in PAMP signaling, and in responses to immunity-related phytohormones such as ethylene, jasmonate, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
164
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(172 citation statements)
references
References 51 publications
4
164
0
4
Order By: Relevance
“…Response to hydrogen peroxide and to both OGs and elf18, as well as to flg22, involves the activation of MPK3 and MPK6 (Zipfel et al, 2006;Galletti et al, 2011;Rasmussen et al, 2012). MPK3 has been shown to be required for basal resistance to B. cinerea and does not significantly affect elicitor-induced resistance , whereas MPK6 is required for elicitor-induced resistance to B. cinerea and full expression of a subset of defense response genes but not for basal resistance to B. cinerea (Galletti et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Response to hydrogen peroxide and to both OGs and elf18, as well as to flg22, involves the activation of MPK3 and MPK6 (Zipfel et al, 2006;Galletti et al, 2011;Rasmussen et al, 2012). MPK3 has been shown to be required for basal resistance to B. cinerea and does not significantly affect elicitor-induced resistance , whereas MPK6 is required for elicitor-induced resistance to B. cinerea and full expression of a subset of defense response genes but not for basal resistance to B. cinerea (Galletti et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…MPK3 and MPK6 are activated also in response to both OGs (Galletti et al, 2011) and elf18 (Zipfel et al, 2006;Rasmussen et al, 2012), and MPK6 has been shown to be required for OG-and flg22-induced resistance to B. cinerea (Galletti et al, 2011). We investigated whether a compromised phosphorylation of MPK3/MPK6 in the anp mutants determines the defect in elicitor-induced defense responses.…”
Section: Anps Act Upstream Of Mpk3 and Mpk6 In The Response To Hydrogmentioning
confidence: 99%
See 1 more Smart Citation
“…It is therefore intriguing that MPK3 and MPK6 were identified as central regulators of plant innate immunity, hypoxia, and salt and osmotic stress responses, which control cross talk between different stresses, hormonal signals, and second messengers, such a ROS (Droillard et al, 2002;Teige et al, 2004;Chang et al, 2012;Rasmussen et al, 2012;Smekalova et al, 2013). MAP kinases were reported to phosphorylate other transcription factors such as WRKY33, which is involved in regulation of ethylene biosynthesis (Li et al, 2012), or MYB44, which regulates abscisic acid sensitivity (Nguyen et al, 2012b).…”
Section: Phosphorylation Of Hsfa4a By Interacting Mpk3 and Mpk6 Kinasesmentioning
confidence: 99%
“…Mitogen-activated protein kinase (MAP kinase) cascades are critically involved in regulating plant defense mechanisms including plant innate immune responses [1]. Studies on the MAP kinase cascade in plants had led to the discovery of groups of genes interacting with each other to activate or inhibit defense related genes such as in pathogenesis related (PR) genes [2].…”
Section: Introductionmentioning
confidence: 99%